The coadministration of N-acetylcysteine ameliorates the effects of arsenic trioxide on the male mouse genital system - Da Silva, Raquel Frenedoso [UNESP]; Borges, Cibele Dos Santos [UNESP]; VillelaE Silva, Patrícia [UNESP]; Missassi, Gabriela [UNESP]; Kiguti, Luiz Ricardo Almeida [UNESP]; Pupo, André Sampaio [UNESP]; Barbosa Junior, Fernando; Anselmo-Franci, Janete Aparecida; Kempinas, Wilma De Grava [UNESP] (Wiley, 2016)
Arsenic trioxide (As2O3) has shown effectiveness in treatment of leukemia but is also associated with reproductive toxicity. Since remediation with N-acetylcysteine (NAC) may mitigate the adverse effects caused by exposure, we assessed the effects of As2O3 and its potential reversibility after exposure cessation or coadministration of NAC. Animals received 0.3 or 3.0 mg/Kg/day of As2O3 subcutaneously and 40 mM of NAC in tap water. As2O3 treatment impaired spermatogenesis and sperm motility and decreased seminal vesicle weight and testosterone serum levels; after suspension of treatment, these parameters remained altered. When NAC was administered, animals showed improvement in sperm parameters and seminal vesicle weight. In vitro epididymal contractility was increased in As2O3-treated animals. We concluded that As2O3 is toxic to the male mouse genital system by compromising sperm quality and quantity; these effects persisted even after suspension of the treatment. However, the coadministration of NAC ameliorates the harmful effects of the drug on the male genital system.